Development of algorithmic and mathematical-logic competences of children in Chile with scratch - Vidal-Silva, C. (2020)
Algorithmic competences for the development of organized operations play an important role in the progress of education and learning of the logical and mathematical reasoning for children. In this context, the visual programming language Scratch is a viable tool for that purpose. Precisely, the main objective of this work is to present experiences and results of the use of that programming language with students of the primary school second year in various Chilean educational institutions, that is, in a public school, in a private school and in a private-subsidized school. These schools are in different geographical areas of the Maule region. Thanks to their social and cultural diversity along with their location, the obtained results are of a great relevance to demonstrate empirically that a significant gap does not exist for the development of algorithmic and logical-mathematical competences in children